Proceedings of the 10th International Workshop on Neutrino-Nucleus Interactions in Few-GeV Region (NuInt15) 2016
DOI: 10.7566/jpscp.12.010039
|View full text |Cite
|
Sign up to set email alerts
|

An Intermediate Water Cherenkov Detector at J-PARC

Abstract: Recent neutrino oscillation results have shown that the existing long baseline experiments have some sensitivity to the effects of CP violation in the neutrino sector. This sensitivity is currently statistically limited, but the next generation of experiments, DUNE and Hyper-K, will provide an order of magnitude more events. To reach the full potential of these datasets we must achieve a commensurate improvement in our understanding of the systematic uncertainties that beset them. This talk describes two propo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A large water tank instrumented with PMTs. This is similar to the TITUS and NuPRISM designs proposed for T2HK [16]. This design could incorporate KM3NeT PMTs as light sensors, thus closely mimicking conditions of the far detector (ORCA).…”
Section: Near Detectormentioning
confidence: 83%
“…A large water tank instrumented with PMTs. This is similar to the TITUS and NuPRISM designs proposed for T2HK [16]. This design could incorporate KM3NeT PMTs as light sensors, thus closely mimicking conditions of the far detector (ORCA).…”
Section: Near Detectormentioning
confidence: 83%
“…The Hyper-Kamiokande (Hyper-K) experiment will use (anti-)ν µ produced from the 1.3MW proton beam at J-PARC to measure the disappearance of (anti-)ν µ and the appearance of (anti-) ν e . The experiment consists of a suite of upgraded T2K near detectors at a baseline of 280 m, a new Intermediate Water Cherenkov Detector (IWCD) [1] at a 1 km baseline and the Hyper-K far detector situated 295 km away. A general overview of Hyper-K sensitivities is given in ref.…”
Section: Introductionmentioning
confidence: 99%
“…The technology in neutrino long baseline experiments has become sophisticated enough that "systematic uncertainties will dominate over statistical uncertainties when measuring neutrino disappearance" [21]. SK itself has an approximate 7% systematic uncertainty event rate prediction for neutrinos launched from the J-PARC particle accelerator.…”
Section: Water Cherenkov Detectorsmentioning
confidence: 99%
“…Given its increased size, HK requires lower systematic uncertainty to progress in the new physics it seeks to study. For example, HK requires a 3% systematic uncertainty rate to acheive sufficient certainty on CP (charge parity symmetry) violation measurements [21]. Abe et al [22] have shown that the addition of a near detector close to (1km or 2km nearby) the neutrino beam source can dramatically lower the event uncertainty on the far detector.…”
Section: Water Cherenkov Detectorsmentioning
confidence: 99%